Transtorno do espectro do autismo na educação infantil: um estudo de caso sobre a gestão de práticas de inclusão - Trindade, Danielli de Oliveira (Universidade do Vale do Rio dos Sinos, 2024)
The increasing number of autistic children included in early childhood school within the Municipal Education Network of Porto Alegre has heightened the demand for the Specialized Educational Assistance (SEA) for the public of the first stage of basic education. The service in question must comply with the regulations and guidelines regarding special education from the perspective of inclusive education. This paper has the objective to present recommendations to qualify the inclusive practices for children with Autism Spectrum Disorder (ASD) in early childhood education schools in the Porto Alegre Municipal Education Network. The methodology adopted was the case study, using semi-structured interviews and document analysis of main legislation ruling special education at both federal and municipal levels, as well as guidelines related to childhood education and to special education of Secretaria Municipal de Educação de Porto Alegre (SMED). Teachers from early childhood schools, from Early Education and Initial Psychopedagogy services, and a representative of the special education management at SMED were interviewed. From the analysis of collected data, the positive evaluation related to effectiveness of the service of Early Education and Initial Psychopedagogy was clear. It was also made explicit the lack of SEA for all the target audience of special education, the SMED’s challenges regarding the processes of monitoring and evaluating inclusive practices and evaluation of inclusive practices and the differences concerning the access and the permanence of autistic children on the municipal and partner networks. As a result of the research, a group of recommendations was drawn up that aim to strengthen the implementation of more inclusive practices that are in line with national and municipal guidelines on the matter. It’s expected that this study will contribute to the advance of knowledge about ASD and enable the improvement of municipal management towards ensuring the right to education in the inclusive perspective in Porto Alegre’s municipal education network, starting from early childhood education.
Keywords: Transtorno do Espectro do Autismo; Inclusão; Educação Infantil; Gestão Educacional; Autism Spectrum Disorder; Inclusion; Early Childhood Education; Educational Management; ACCNPQ::Ciências Humanas::Educação